2019
DOI: 10.1007/s12525-019-00328-z
|View full text |Cite
|
Sign up to set email alerts
|

Focusing the customer through smart services: a literature review

Abstract: Smart services serve customers and their individual, continuously changing needs; information and communications technology enables such services. The interactions between customers and service providers form the basis for co-created value. A growing interest in smart services has been reported in the literature in recent years. However, a categorization of the literature and relevant research fields is still missing. This article presents a structured literature search in which 109 relevant publications were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 97 publications
0
48
0
2
Order By: Relevance
“…Several regulatory compliances and government regulations have been established to address the growing threats to privacy and security. For instance, the European Union has implemented the General Data Protection Regulation (GDPR) requiring measures to protect citizens within the EU [62]. From the practical perspective (i.e., considering government regulations), SH provider should react to users' privacy concerns to comply with government regulations such as the GDPR to avoid any legal complications through the use of SH devices and the associated personal data.…”
Section: Implications and Recommendations For Research And Practicementioning
confidence: 99%
“…Several regulatory compliances and government regulations have been established to address the growing threats to privacy and security. For instance, the European Union has implemented the General Data Protection Regulation (GDPR) requiring measures to protect citizens within the EU [62]. From the practical perspective (i.e., considering government regulations), SH provider should react to users' privacy concerns to comply with government regulations such as the GDPR to avoid any legal complications through the use of SH devices and the associated personal data.…”
Section: Implications and Recommendations For Research And Practicementioning
confidence: 99%
“…The former (a) support practitioners by providing guidelines for the development and lifecycle management [9], [10], [23], analyzing the requirements and impacts [9], [24], or developing useable infrastructure [25]. The latter (b) analyze and integrate literature [3], [26], examine the state of the art in practice [19], [27] and literature, and discuss and conceptualize smart services [2], [6].…”
Section: Smart Service Systems In Manufacturing In the Scientific Litmentioning
confidence: 99%
“…Smart service systems are service systems in which smart products are boundary objects that integrate resources and activities of the involved actors for mutual benefit. Dreyer et al (2019) Smart services are individual, highly dynamic and quality-based service solutions that are convenient for the customer, realized with field intelligence and analyses of technology, environment and social context data (partially in real-time), resulting in co-creating value between the customer and the provider in all phases from the strategic development to the improvement of a smart service.…”
Section: Strategies For Smart Servicesmentioning
confidence: 99%
“…-The fourth paper comprises a literature review on how smart services enable the customer perspective and sheds light on the research directions that may be observed in the literature. The authors Sonja Dreyer, Daniel Olivotti, Benedikt Lebek and Michael H. Breitner identify a total of 13 topics across five phases of the smart service lifecycle (Dreyer et al 2019). The results reveal that economic aspects and the role of the customer receive only inferior attention.…”
Section: Special Issue Papersmentioning
confidence: 99%
See 1 more Smart Citation